Find all continuous functions f : R → R such that f ( f ( x + y ) ) = f ( x ) + f ( y ) and f ( x ) = 0 and f ( 1 0 1 0 ) = 1 0 1 1 . In particular, what is f ( 2 0 2 0 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let
P
(
x
,
y
)
be the statement
f
(
f
(
x
+
y
)
)
=
f
(
x
)
+
f
(
y
)
(
1
)
.
Moreover, let
f
(
0
)
=
c
.
P
(
x
+
y
,
0
)
⇒
f
(
f
(
x
+
y
)
)
=
f
(
x
+
y
)
+
c
(
2
)
( 1 ) , ( 2 ) ⇒ f ( x + y ) + c = f ( x ) + f ( y ) ( 3 )
Let
g
(
x
)
=
f
(
x
)
−
c
,
x
∈
R
.
Then,
(
3
)
⇒
f
(
x
+
y
)
−
c
=
(
f
(
x
)
−
c
)
+
(
f
(
y
)
−
c
)
⇒
g
(
x
+
y
)
=
g
(
x
)
+
g
(
y
)
.
Thus,
g
satisfies
Cauchy’s functional equation
. Since
f
is continuous, the same holds for
g
. It is well known that any continuous solution to Cauchy’s equation is of the form
g
(
x
)
=
k
x
, for some
k
∈
R
.
This implies that f ( x ) = k x + c , x ∈ R .
Now,
P
(
x
,
0
)
⇒
f
(
f
(
x
)
)
=
f
(
x
)
+
c
⇒
k
⋅
f
(
x
)
+
c
=
k
x
+
2
c
⇒
k
⋅
(
k
x
+
c
)
+
c
=
k
x
+
2
c
⇒
k
2
x
+
k
c
=
k
x
+
c
⇒ { k 2 = k k c = c ⇒ ( { k = 0 c = 0 o r { k = 1 c ∈ R )
Since
f
is not the zero function, the first option is rejected. Hence,
f
(
x
)
=
x
+
c
,
x
∈
R
.
Plugging
x
=
1
0
1
0
, we get
f
(
1
0
1
0
)
=
1
0
1
0
+
c
⇒
1
0
1
1
=
1
0
1
0
+
c
⇒
c
=
1
.
We can easily verify that
f
(
x
)
=
x
+
1
satisfies all given conditions.
Thus, this is the unique solution to the problem.
For the answer, f ( 2 0 2 0 ) = 2 0 2 1 .
Problem Loading...
Note Loading...
Set Loading...
We claim that the only solution is f ( x ) = x + 1 . Let P ( x , y ) be the assertion, using P ( x + y , 0 ) and P ( x , y ) , we can easily get f ( x + y ) + f ( 0 ) = f ( x ) + f ( y ) and then let g ( x ) = f ( x ) − f ( 0 ) , g ( x + y ) = g ( x ) + g ( y ) since f is continuous, g is also continuous and thus g is linear. Thus, f ( x ) = k x + c where k , c ∈ R . Then we can find that when k = 1 , since f ( 1 0 1 0 ) = 1 0 1 1 , we must have c = 1 . So, the only solution is f ( x ) = x + 1 ∀ x ∈ R . Hence, f ( 2 0 2 0 ) = 2 0 2 1 .